“[...] Ele precisa de um espaço para falar do jeito dele, né? ”: a sala de recurso multifuncional e seu papel no desenvolvimento da linguagem de alunos indicados para atendimento educacional especializado - Bandeira, Vanessa Suzani da Silva (Universidade do Vale do Rio dos Sinos, 2020)
The multifunctional resource room (MRR) has the propose of identifying, elaborating and organizing pedagogical and accessibility resources to reduce barriers to the full participation of students with disabilities, global developmental disorders, high skills and giftedness, considering their specificities according to the SEESP/GAB Technical Note/ nº 11/2010 (BRAZIL, 2010). The MRR receives the indication from elementary school teachers of students who still do not know how to read and write, for service. From this demand, the main objective of this research is to analyze how language, teaching and intellectual disability are evidenced in the speech of five teachers who work in the multifunctional resource room, aiming at the learning of students received in this space. This study uses a qualitative methodology of ethnographic nature (FLICK, 2009; CRESWELL, 2014), with data generated from a semi-structured interview, recorded on audio, with the respective teachers of a city of Vale do Rio dos Sinos, Brazil. The data were analyzed from theoretical assumptions of Vygotsky (2008), Volochinov (2017), Haag (2015), based on a concept of language as interaction. Kleiman (2015), Rojo and Moura (2019), and Santaella (2003) are prominent authors in terms of the perspective of teaching literacy and multi-literacy, and Lopes (2007) and Klein (2015) are references for discussion on in/exclusion. The multifunctional resource room is a space that articulates with different professionals who work with the received students. Thus, MRR can contribute to the affirmation of a disability network that involves the student or can enhance the teaching-learning process in a way that the student rescues the belief in himself and advances in this process. In this way, it is evident that the MRR is able to establish itself in the school environment as a field of potentiation of students who present differences in learning, guaranteeing, through practical activities in the perspective of multiliteracies, a place closer to social inclusion.
Keywords: Sala de recurso multifuncional; Linguagem; Ensino; Deficiência intelectual; Multiletramentos; Multifunctional resource room; Language; Teaching; Intellectual disability; Multiliteracies; ACCNPQ::Lingüística, Letras e Artes::Lingüística